2013
DOI: 10.14219/jada.archive.2013.0212
|View full text |Cite
|
Sign up to set email alerts
|

Association of smokeless tobacco use and smoking in adolescents in the United States

Abstract: Background Using smokeless tobacco and smoking are risk behaviors for oral cancer, soft tissue lesions, caries, periodontal disease and other oral conditions. The purpose of this study was to examine adolescent smokeless tobacco use and smoking. Methods The study was a cross-sectional analysis of participants with complete data on smoking, smokeless tobacco use, and other variables of interest in the 2011 Youth Risk Behavior Survey (n=9655). Descriptive analysis and multivariable logistic regression analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Using published cut points for “positive screens” or values that would warrant further discussion, (Cella et al 2012; Coleman et al 2012; Kroenke et al 2009; Paxton et al 2011; Rohrer et al 2009; Smith et al 2009, 2010; Snowden et al 2011; Wiener 2013), we calculated the proportion of respondents who would qualify for primary care intervention for each health behavior and mental health measure. We calculated the frequency of each positive screen and total number of positive screens per patient for each practice and for subgroups of practices (FQHC vs. PBRN vs. VA).…”
Section: Methodsmentioning
confidence: 99%
“…Using published cut points for “positive screens” or values that would warrant further discussion, (Cella et al 2012; Coleman et al 2012; Kroenke et al 2009; Paxton et al 2011; Rohrer et al 2009; Smith et al 2009, 2010; Snowden et al 2011; Wiener 2013), we calculated the proportion of respondents who would qualify for primary care intervention for each health behavior and mental health measure. We calculated the frequency of each positive screen and total number of positive screens per patient for each practice and for subgroups of practices (FQHC vs. PBRN vs. VA).…”
Section: Methodsmentioning
confidence: 99%
“…This nding is not surprising given that the etiology of oral cancer is complex, and some potential confounders were not controlled for due to a lack of such information, including alcohol consumption and HPV infection. Previous studies have found that users of ST were more likely to be heavier alcohol drinkers [44,45]. Furthermore, the existing evidence points to a positive association between tobacco use and HPV [46].…”
Section: Discussionmentioning
confidence: 99%
“…Free nicotine (unionized and PH above 6.5) is readily absorbed into biological tissues, and well absorbed through the mouth and buccal membranes. The significance of the transfer of tobacco-related constituents and toxicants across oral mucosal membranes increases the potential for systemic diseases, oral diseases and many forms of cancer [18][19][20]. Constituents cross oral mucosal membranes, enter the bloodstream and subsequently the brain where is exerts the pharmacological effects that may lead to addiction [20].…”
Section: American Journal Of Biomedical Science and Researchmentioning
confidence: 99%
“…The significance of the transfer of tobacco-related constituents and toxicants across oral mucosal membranes increases the potential for systemic diseases, oral diseases and many forms of cancer [18][19][20]. Constituents cross oral mucosal membranes, enter the bloodstream and subsequently the brain where is exerts the pharmacological effects that may lead to addiction [20]. The results of two studies by Hatsukami.…”
Section: American Journal Of Biomedical Science and Researchmentioning
confidence: 99%